ENHANCING LEARNER’S READING COMPETENCY THROUGH PROJECT-BASED PRE-COOPERATIVE MULTILITERACY (Descriptive Study at CLC Hikmah District. Ciamis, CLC Al-Ghifari District. Cirebon, and CLC Geger Sunten District. West Bandung) - Neni Nurlaela (IKIP Siliwangi Bandung, 2020)
Education multiliteracy is an education that emphasizes on increasing the diversity of literacy in all aspects of life. The multiliteracy education program is a program of literacy by using a variety of approaches (arts, culture, environment, technology, race, ethnicity, gender, and others) are relevant to the learners to achieve and or develop literacy competencies and improve the income and quality of life of participants students. The focus of the problem is as follows: How to increase literacy skills of reading advanced literacy students through Project-based multiliteracy learning models in CLC Hikmah District. Ciamis, CLC Al-Ghifari District. Cirebon, and CLC Geger Sunten District. West Bandung? The project-based multiliteracy pre-cooperative learning model is multiliteracy learning with the theme of science and technology pre-cooperative sub-themes using project-based learning strategies. Learners during learning in enhancing the ability of literacy such as reading, writing, and arithmetic in the language of Indonesia to be given charge of pre cooperatives. Wherein the output of this study is the formation of pre-cooperative business groups, in the process of establishing this cooperative course pre herded learners to complete the project in any appropriate syntax learning project-based learning, namely: 1) Determination of project. 2) Designing project completion steps. 3) Compilation of project implementation schedules. 4) Project completion. 5) Report preparation. 6) Evaluate the process and process results.Based on the research results obtained Asymp.sig (2-tailed) = 0,000 <0.05 then Ho is rejected and Ha is accepted meaning there is an average difference between the pre-test and post-test learning outcomes, which means there is an influence on the use of the Project-based pre-cooperative multi-literacy model towards increased literacy skills in reading students.